2014
DOI: 10.1002/pen.24049
|View full text |Cite
|
Sign up to set email alerts
|

Vulcanization of EPDM rubber compounds with and without blowing agents: Identification of reaction events and TTT-diagram using DSC data

Abstract: Vulcanization of industrial‐like ethylene propylene diene termonomer rubber compound is studied using a differential scanning calorimetry (DSC). The analysis starts with DSC information to obtain the total transformation heat, followed by an isothermal‐dynamic temperature ramp that captures diffusion‐controlled reaction kinetics. The vulcanization is modeled by an auto‐catalytic Kamal–Sourour model, complemented with a Kissinger model for the prediction of one energy of activation, DiBenedetto's equation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 68 publications
2
37
0
3
Order By: Relevance
“…The first region is the induction period, when most of the accelerator reactions occur; this is followed by the curing and postcuring regions. A relationship that describes the dependence of t o on the absolute temperature ( T ) was proposed by Claxton and Liska as follows: to=BO eAOT where B O is the pre‐exponential factor and A O is a material constant independent of the temperature. The effect of the temperature on t o is reported in Figure , where the test temperatures are given in degrees Kelvin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first region is the induction period, when most of the accelerator reactions occur; this is followed by the curing and postcuring regions. A relationship that describes the dependence of t o on the absolute temperature ( T ) was proposed by Claxton and Liska as follows: to=BO eAOT where B O is the pre‐exponential factor and A O is a material constant independent of the temperature. The effect of the temperature on t o is reported in Figure , where the test temperatures are given in degrees Kelvin.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from these proposed curing kinetics models, the relationship between the reaction mechanism and the network structure of the resulting compounds have not yet been conclusively clarified because of the complexity of the chemical reactions that take place during the curing reaction. k 1 characterizes the initial reactivity, including the effect of the catalysts (accelerators and activators in the rubber compound), and k 2 characterizes the autocatalytic effect of the groups generated during the reaction …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we extended the experimental method proposed by Hernandez‐Ortiz and Osswald and later improved by Restrepo‐Zapata et al . This method to obtain TTT‐diagrams is based on non‐isothermal and quasi‐isothermal DSC measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The glass transition temperature, T g , is required to model partial diffusion control. This method was used to characterize polyester, linseed‐based epoxy, and ethylene propylene diene monomer (M‐class), EPDM, rubber . This study showed that their method works for epoxy film adhesives.…”
Section: Methodsmentioning
confidence: 99%